Measurement of temperature and displacement with NiTi actuators under certain electrical conditions - TOPTAŞ, ERSİN; ÇELEBİ, MEHMET FATİH; ERSOY, SEZGİN (JVE INT LTD, 2021)
In this study, various mechanical behaviors of a shape memory alloy, depending on different thermal and electrical conditions to be used in areas such as biomedical, aerospace and aeronautics. Temperature changes and length change rates under different electrical current values of a shape memory alloy named nickel titanium, or nitinol (NiTi) has been observed. It has been seen that a 0.3 mm diameter wire can generate a force of 25 N while the material extends its linear measurement with a rate of 3.7 mm/s. It is observed that, under diverse constant electrical current values, the displacement and temperature relations of the nickel titanium wire is varying. It has empirically been seen that the nickel titanium alloy actuators are advantageous than their alternatives in terms of the generated strength to weight ratio and shape memory alloy materials can be used as actuators in industrial and biomedical applications.
Keywords: actuators; shape memory alloys; sma; nickel titanium; niti; nitinol; biocompatibility